A Journey of Nanomotors for Targeted Cancer Therapy: Principles, Challenges, and a Critical Review of the State‐of‐the‐Art. Issue 2 (27th October 2020) - Wang, Wei; Zhou, Chao
Abstract: A nanomotor is a miniaturized device that converts energy stored in the environment into mechanical motion. The last two decades have witnessed a surge of research interests in the biomedical applications of nanomotors, but little clinical translation. To accelerate this process, targeted cancer therapy is used as an example to describe a "survive, locate, operate, and terminate" (SLOT) mission of a nanomotor, where it must 1) survive in the unfriendly in vivo environment, 2) locate its target as well as be located by human operators, 3) carry out specific operations, and 4) terminate after the mission is completed. Along this journey, the challenges presented to a nanomotor, including to power, navigate, steer, target, release, control, image, and communicate are discussed, and how state‐of‐the‐art nanomotors meet or fall short of these requirements is critically reviewed. These discussions are then condensed into a table for easy reference. In particular, it is argued that chemically powered nanomotors are intrinsically ill‐positioned for targeted cancer therapy, while nanomotors powered by magnetic fields or ultrasound show more promises. Following this argument, a tentative nanomotor design is then presented in the end to conform to the SLOT guideline, and to inspire practical, functional nanorobots that are yet to come. Abstract : Focusing on targeted cancer therapy, this article highlights the challenges of a nanomotor during an in vivo mission to survive, locate, operate and terminate (SLOT). A survey of the state‐of‐the‐art suggests that nanomotor designs that truly conform to all aspects of a SLOT mission are still lacking, and externally powered nanomotors are better than those powered by chemistry for operations in bloodstream.